The Relationship between the Implementation of Nursing Supervision with the Performance of Nursing in Patient Room at Dumai City General Hospital - Suci Amin; Dilgu Meri; Dewi Anggraini (Universitas STRADA Indonesia, 2022)
An assurance for the patients' health care is a nurse's quality care. In order to maintain the standard of care provided in a unit, one of the managerial responsibilities of a nurse manager is to oversee the nurses. The goal of this study was to ascertain how well nurses performed in the inpatient unit of Dumai City General Hospital in relation to the use of nursing supervision. With samples of 118 nurses, the research design described cross-sectional correlation. The research tool was a questionnaire with a 57.1% supervision and a 43.9% performance ratio. Purposive sampling was used to take the sample. The findings of the chi square analysis revealed a relationship between the performance of the nurses in the inpatient room at Dumai City General Hospital and the supervision provided by the nurse management (p=0,000=0,05). The administration of Dumai City General Hospital is hoped to strengthen nursing supervision activities in order to enhance the performance of the nurses in providing patient care.